The molecular design of cage metal complexes for biological applications: pathways of the synthesis, and X-ray structures of a series of new N2-, S2- and O2-alicyclic iron(ii) di- and tetrachloroclathrochelates. (27th November 2017) - Zelinskii, Genrikh E.; Belov, Alexander S.; Belaya, Irina G.; Vologzhanina, Anna V.; Novikov, Valentin V.; Varzatskii, Oleg A.; Voloshin, Yan Z.
Abstract : New iron(ii ) di- and tetrahalogenoclathrochelates with apical functionalizing substituents were prepared and characterized. Abstract : The synthesis of new metal(ii ) di- and tetrahalogenoclathrochelates with apical functionalizing substituents as reactive macrobicyclic precursors is a key stage of the molecular design of cage metal complexes – prospective biological effectors. We found that the most convenient multistep synthetic pathway for their preparation includes (i) direct template condensation of a dihalogeno-α-dioxime with an appropriately functionalized boronic acid on the corresponding metal ion as a matrix, giving an apically functionalized metal hexahalogenoclathrochelate in a high yield; and (ii) its stepwise nucleophilic substitution with S 2 -, N 2 - or O 2 -bis-nucleophiles, forming stable six-membered alicyclic ribbed fragments, thus allowing obtaining the corresponding apically functionalized di- and tetrahalogenoclathrochelates. The latter reaction of an iron(ii ) hexachloroclathrochelate with different N 2 -, S 2 - and O 2 -bis-nucleophilic agents afforded chloroclathrochelate complexes with equivalent and non-equivalent alicyclic ribbed substituents, such as N 2 -, S 2 or O 2 -containing six-membered cycles. In the case of anionic forms of pyrocatechol and 1, 2-ethanedithiol as O 2 - and S 2 -bis-nucleophiles, generated in situ in the presence of triethylamine, such substitution proceeds easily and in a high yield. In the case of anionic derivatives of ethylenediamine as N 2 -bis-nucleophiles, only a mono- N 2 -alicyclic iron(ii ) tetrachloroclathrochelate was obtained in a moderate yield. The S 2 -alicyclic iron(ii ) tetrachloroclathrochelate underwent a further nucleophilic substitution of one of the two dichloroglyoximate fragments, giving its N 2, S 2 -alicyclic dichloroclathrochelate derivative with three non-equivalent ribbed chelate fragments. The complexes obtained were characterized using elemental analysis, MALDI-TOF mass spectrometry, and IR, UV-vis, 1 H and 13 C{ 1 H} NMR spectroscopies, and by single crystal X-ray diffraction (XRD). As follows from XRD data for four O 2 -, S 2 - and N 2 -ribbed-functionalized iron(ii ) clathrochelates, the geometry of their FeN6 -coordination polyhedra is intermediate between a trigonal prism and a trigonal antiprism. UV-vis spectra of these cage complexes are indicative of a dramatic redistribution of the electron density in a quasiaromatic clathrochelate framework caused by its ribbed functionalization with six-membered O 2 -, S 2 - and/or N 2 -alicyclic substituent(s).